Madrasah's Leadership Strategy in Improving the Quality of Online Learning During Pandemic - Muhammad Rizki Syahputra; Sudirman (EDUTEC : Journal of Education And Technology, 2021)
This study aims to determine how the headmaster's leadership strategy is in improving the quality of online learning during the Coronavirus Disease (Covid-19) pandemic at MTs Negeri 2 Langkat Regency. naturalistic which means observing a problem subject that arises naturally. The collected data are in the form of narration, text, written, spoken or in the form of pictures. Qualitative research is conducted to understand the activities, behavior and ways of life of other people, social or other natural symptoms. The strategy of the madrasah principal is the key to success in achieving the stated goals of the madrasah. The head of the madrasah as the highest leader in the education unit actually has visionary thoughts in developing the madrasah he leads, such as having a precise strategy in advancing his madrasah. Without a strategy, the madrasah program will not work. Strategy is the first and most important step when a leader intends to advance the madrasa. During the Covid-19 pandemic the learning process could not be stopped even though educational institutions were temporarily closed, face-to-face learning was not allowed, so online learning was implemented where activities were carried out from home. The strategy of the madrasa principal is to implement several applications such as 1) Zooom Meeting, 2) Google Classroom, 3) Google Meet, 4) WhatsApp Group, and 5) Email in supporting the online learning process at MTs Negeri 2 Langkat Regency. This strategy is a solution for students during the Covid-19 pandemic, students can learn from home online, so that they can interact via the media and can receive subject matter provided by the teacher.